APLIKASI PUPUK MONO KALIUM PHOSPHATE (MKP) DAN KONSENTRASI EM4 TERHADAP PERKEMBANGAN PERTUMBUHAN TANAMAN CABAI PAPRIKA (Capsicum annum L.) - Rahmiati, Rahmiati; Bustami, Bustami; Hayati, Rahmah; Nastasya, Widia (AGROSUSTAIN, 2023)
Application of Mono Potassium Phosphate Fertilizer (MKP) and EM4 Concentration on the Growth Development of Chili Peppers (Capsicum annum L.). The purpose of this study was to determine the application of MKP fertilizer and EM4 concentration on the growth development of chili peppers (Capsicum annum L.). This research was carried out at the Research Field of the Faculty of Agriculture on Jalan Sultan Iskandar Muda Airport, Blang Bintang District, Aceh Besar District, Cot Karieng Village, Aceh Besar Province. The research time was ± 3 months, starting from the beginning of November 2021 to the end of January 2023. This study used a Completely Randomized Design (CRD) 4x4 Factorial Pattern with 3 replications. The first factor was the concentration of mono potassium phosphate (MKP) fertilizer with 4 levels, namely: M0 = control, M1 = 250 ml of water, M2 = 500 ml of water, M3 = 750 ml of water. The second factor was the concentration of EM4 consisting of 4 levels, namely: E0 = control, E1 = 5 ml of water, E2 = 10 ml, E3 = 15 ml of water. The results showed that the concentration of mono Potassium Phosphate (M) had a significant effect on fruit length observations, but had no significant effect on plant height observations at 15, 30, 45 and 60 days after planting. And did not significantly affect the observation of plant height 15 and 30 days after planting and fruit length observations. There was an interaction that had a very significant effect due to the concentration of mono potassium phosphate (M) fertilizer and the concentration of EM4 (E) which had a significant effect on the observation of fruit length. And did not significantly affect the observation of plant height aged 15, 30, 45 and 60 days after planting.